Influence of clay dispersion on flame retardancy of ABS/PA6/APP blends. (April 2015) - Lu, Chang; Liu, Lin; Chen, Nian; Wang, Xiao; Yang, Dian; Huang, Xin-hui; Yao, Da-hu
Abstract: Influence of dispersion of clay in acrylonitrile–butadiene–styrene/nylon-6 (ABS/PA6) blends on flame retardancy was investigated. The results of FTIR spectra and transmission electron microscopy (TEM) showed that ammonium polyphosphate (APP) and clay were exclusively dispersed in the PA6 phase. Clay modified with poly (styrene- co -maleic anhydride) (SMA) was selective localization at the interface of blends. Introduction of clay and modified clay to blends caused the dispersion of clay not only in PA6 phase, but also at the interface. The flame retardancy was evaluated by limiting oxygen index (LOI), vertical flammability test, and cone calorimeter tests. For the blends with dispersed PA6 phase, the dispersion of clay only in PA6 phase or at interface had negative effect on flame retardant property. Morphology of residue char characterized by scanning electron microscope (SEM) showed that the inhibition of clay platelets on the expansion of residue char should be responsible for the deterioration of flame retardant properties. When clay dispersed both in PA6 phase and at the interface, the reinforcement of clay platelets on residue char caused the formation of compact and continuous superficial char, resulting in significant improvement of flame retardancy. In blends with continuous PA6 phase, introducing clay to blends caused the formation of compact and continuous superficial char thus improved the flame retardancy no matter where the clay dispersed in blends. The characterization of energy dispersive spectrometry (EDS) revealed that the morphology of char was determined by the dispersion of clay platelets in residue char.